Development of an Antimicrobial Material Made of Graphene Oxide, Polylactic Acid/Polyhydroxybutyrate, and Cuo Nanoparticles and Its Reprocessing Effect on Its Properties - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (John Wiley and Sons Inc, 2025)
In the present study nanocomposites made of polylactic acid (PLA), polyhydroxybutyrate (PHB), graphene oxide (GO), and copper (II) oxide (CuO) nanoparticles on three compositions (1, 3 and 5 wt%), obtained through melt extrusion were developed. Properties of the nanocomposites obtained in their first and second processing were evaluated, and characterized through colorimetry L*a*b*, Fourier-transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), Differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), mechanical properties (ASTM D638 standard), scanning electron microscopy–energy-dispersive x-ray spectroscopy (SEM-EDX) and antimicrobial activity under dynamic contact with ATCC25922 Escherichia coli. The obtained results of the first processing presented variations in color and crystallinity between different nanocomposites. Additionally, a higher antimicrobial activity was observed in the nanocomposites containing CuO, achieving up to 100% bacterial reduction at 3% nanoparticle content. When evaluating the influence of the second nanocomposites thermic processing, it could be seen an acceleration of the degradation process of the polymeric chains in addition to an improvement in the dispersion of the nanoparticles, which reduced their agglomeration and generated variations on the crystalline state of the nanocomposites. Highlights: The nanocomposites exhibit high antimicrobial activity. GO and CuO nanoparticles show a tendency to agglomerate. Reprocessing induces chain scission. Reprocessing also enhances matrix homogenization. The dispersion of the nanofiller reduced antimicrobial activity. © 2025 Society of Plastics Engineers.